2012
DOI: 10.1530/jme-12-0039
|View full text |Cite
|
Sign up to set email alerts
|

DPP4 inhibitor vildagliptin preserves β-cell mass through amelioration of endoplasmic reticulum stress in C/EBPB transgenic mice

Abstract: The development of type 2 diabetes is accompanied by a progressive decline in b-cell mass and function. Vildagliptin, a dipeptidyl peptidase 4 inhibitor, is representative of a new class of antidiabetic agents that act through increasing the expression of glucagon-like peptide-1. The protective effect of this agent on b cells was studied in diabetic mice. Diabetic pancreatic b cell-specific C/EBPB transgenic (TG) mice exhibit decreased b-cell mass associated with increased apoptosis, decreased proliferation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…Previous reports also indicate that inhibition of DPP-4 directly regulates the endothelial cell growth and migration induced by inflammatory cytokines (32). In the present study, vildagliptin increased circulating GLP-1 levels 1.8-fold in WT mice, in agreement with previous reports (27,33). In HUVECs, GLP-1 enhanced AkteNOS signaling and promoted the formation of capillary-like structures to a greater extent than vildagliptin, but the ability of vildagliptin to mediate these effects with no GLP-1 in HUVECs suggests that the vasculo-protective effects of vildagliptin occur at least partially through a mechanism that is independent of GLP-1.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous reports also indicate that inhibition of DPP-4 directly regulates the endothelial cell growth and migration induced by inflammatory cytokines (32). In the present study, vildagliptin increased circulating GLP-1 levels 1.8-fold in WT mice, in agreement with previous reports (27,33). In HUVECs, GLP-1 enhanced AkteNOS signaling and promoted the formation of capillary-like structures to a greater extent than vildagliptin, but the ability of vildagliptin to mediate these effects with no GLP-1 in HUVECs suggests that the vasculo-protective effects of vildagliptin occur at least partially through a mechanism that is independent of GLP-1.…”
Section: Discussionsupporting
confidence: 93%
“…We therefore assessed plasma levels of active GLP-1, SDF-1␣, and adiponectin in WT mice treated with or without vildagliptin for 7 and 21 days after induced hind limb ischemia. Vildagliptin treatment did not affect blood glucose levels on days 7 and 21 following surgery in non-diabetic WT mice, as described in previous reports (27). There were significant increases in active GLP-1 and adiponectin, but not SDF-1␣ in the plasma of WT mice following treatment with vildagliptin compared with treatment with vehicle control on postoperative days 7 and 21 (Table 1).…”
Section: Vildagliptin Enhances Ischemia-induced Revascularization In supporting
confidence: 78%
“…Shimizu et al developed pancreatic β-cell-specific C/EBPB transgenic mice and showed that GLP-1, the circulating level of which was increased by DPP-4 inhibitor through inhibiting degradation, induced C/ EBPB degradation, leading to the attenuation of endoplasmic reticulum stress in β-cells. 20 However, an additive effect of ARBs and DPP-4 inhibitors on β-cell function has not been fully investigated. Wang et al demonstrated that combination treatment of GLP-1 and the ARB candesartan exerted an additive anti-apoptotic effect in isolated mouse pancreatic islets.…”
Section: Discussionmentioning
confidence: 99%
“…In streptozotocin (STZ)-treated diabetic mice and other models of b-cell insufficiency, early administration of either a GLP1R agonist or a DPP4 inhibitor is able to preserve a greater b-cell mass. (vildagliptin, des-fluoro-sitagliptin and NVP-DPP728) for 2-5 months in young chow-fed C57BL/6 mice did not increase b-cell mass (Reimer et al 2002, Rankin et al 2012, Shimizu et al 2012. Only one of these studies reported a slight increase in b-cell proliferation with des-fluoro-sitagliptin treatment, but it was only a fraction of the increase observed with high-fat feeding alone (Rankin et al 2012).…”
Section: Dpp4 Inhibitors and B-cell Massmentioning
confidence: 99%
“…In a mouse model that expresses hIAPP at levels roughly equal to those of the endogenous mouse protein, sitagliptin treatment for 1 year was able to maintain b-cell mass at levels that were very similar to those in the non-transgenic control mice (Aston-Mourney et al 2013). In other genetically modified animals, such as the Irs2 knockout and Cebpb transgenic mice, vildagliptin treatment (0.3 mg/ml in drinking water) for 20 weeks in both these strains was able to increase b-cell mass to levels approaching those observed in normal mice, and this was associated with either a reduction in apoptosis or an increase in b-cell proliferation (Sato et al 2012, Shimizu et al 2012. In Gck-deficient mice, sitagliptin treatment for 20 weeks was able to maintain almost normal b-cell mass, which was accompanied by a reduction in the rates of b-cell apoptosis and a small increase in proliferation (Shirakawa et al 2011a).…”
Section: Can Dpp4 Inhibitors Affect B-cell Mass In Transgenic or Knocmentioning
confidence: 99%